Genetic susceptibility to coronary artery disease in Bangladesh: evaluation of MTHFR gene polymorphisms (C677T and A1298C) and hyperhomocysteinemia as independent risk factors of coronary artery disease among young Bangladeshi adults - Alabbi, Mysha Nowrin; Malek, Naila Masfiqua; Nanziba, Rifah (Brac University, 2024)
This thesis submitted to the Department of Mathematics and Natural Sciences in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2024.